PENGGUNAAN NON ZERO DISPERSION SHIFTED FIBER PADA TRANSMISI KOMUNIKASI SERAT OPTIK KANAL 40 Gbit/s - Harumi Yuniarti; Bambang Cholis S (Website, 2013)
Abstract Optical fiber transmission is generally used when the channel capacity (40 Gbit / s). Some of the key factors in achieving successful performance of this system include the implementation of Apol-DPSK modulation technique (Alternate Polarization Return-to-Zero Differential Phase Shift Keying), which accurately able to power up the canal, placement of optical amplifier (repeater) is recommended to increase the transmission range (the average gain for the entire wavelength range, low noise figure) and the use of optical fiber characteristics. To complement performance optical gain is selected fiber types NZDSF (Non-Zero Dispersion shifted fiber), it certainly can provide significant gains at the same time to reduce the widening pulse narrowing occurs due to chromatic dispersion and non-linear fiber effects. Keywords: Apol-RZDPSK, EDFA, RFA, DRA, NZDSF, PMD.